Hubungan Pengetahuan Keluarga dengan Tingkat Kecemasan pada Anggota Keluarga yang Dirawat di Ruang ICU dan ICCU Rumah Sakit Umum Daerah Meuraxa Kota Banda Aceh - M. Kamal Radadi; Fauziah Fauziah; Mansuriza Mansuriza (Inovasi Kesehatan Global, 2025)
The admission of patients to the Intensive Care Unit (ICU) or Intensive Cardiology Care Unit (ICCU) often occurs suddenly and under critical conditions, causing family members to experience psychological pressure such as anxiety, stress, and fear of losing their loved ones. This study aims to analyze the relationship between family knowledge and the level of anxiety among family members of patients treated in the ICU at Meuraxa General Hospital, Banda Aceh. The research employed a quantitative method with a descriptive correlational design and a cross-sectional approach. The population consisted of 114 patient families, with 35 respondents selected through purposive sampling. The instrument used was the Hamilton Anxiety Rating Scale (HARS), which demonstrated high reliability (α = 0.897). Data were collected from June 18 to July 5, 2025, and analyzed using univariate and bivariate methods with the chi-square test. The results showed that 19 respondents (54.3%) experienced moderate anxiety, while 14 respondents (40%) had low knowledge regarding ICU/ICCU care. Statistical analysis revealed a p-value of 0.005, indicating a significant relationship between family knowledge and anxiety levels. These findings highlight the importance of healthcare professionals in providing education to family members to improve understanding and help reduce anxiety during the patient’s treatment period in the ICU or ICCU.